KH. ACHMAD ZAMACHSYARI, LEADERSHIP, AND MODERNIZATION OF PESANTREN: Character Study in Al-Rifa’ie Modern Islamic Boarding School of Malang - Pramitha, Devi (ULUL ALBAB Jurnal Studi Islam, 2021)
KH. Achmad Zamachsyari or Gus Mad became one of the initiators to make changes by establishing a modern Islamic boarding school in Malang. He leads, provides a vision to move toward improvement and change. He chose an area in Ketawang, Gondanglegi, Malang to begin his struggle to build a modern Islamic boarding school. This study aims at obtaining a complete description of Gus Mad's leadership behavior; his interaction patterns; and modernization concept of Islamic boarding school education. The research design is qualitative and it uses the character study method. Gus Mad was chosen as the object of research because he was one of the Kiais in Malang who made a change, namely from the leader of the Al-Fattah Singosari Salafiyah then founded the Al-Rifa'ie Modern Islamic boarding school. Data obtained by interviews, documents, and observation. Data analysis used the Spradley model, consisting domain, taxonomic, component and theme analyses. Three findings are (1) Gus Mad's behavior at Al-Rifa'ie leads to transformational leadership; (2) his interaction pattern at Al-Rifa'ie led to traditional leadership; and (3) hisconcept of modernization of Islamic boarding school education is based on the principles of al-Muḥâfaẓat ‘alâ al-qadîm al-ṣâliḥ wa al-akhdhu bi al-jadîd al-aṣlaḥ. Gus Mad’s leadership style at Al-Rifa'ie Modern Islamic Boarding School Malang is a neo-transformationalism leadership style, a combination of transformationalism and traditionalism leadership style based on the principles of al-muḥâfaẓat ‘alâ al-qadîm al-ṣâliḥ wa al-akhdhu bi al-jadîd al-aṣlaḥ.